Marginalisasi Perempuan Dalam Novel Nyutrayu Karya Joko Gesang Santoso - Zahrotul Mawaddah; Harjito Harjito; Ika Septiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this research is to describe the marginalization of women in the novel